Distributed robust time-efficient broadcasting algorithms for multi-channel wireless multi-hop networks with channel disruption - Tian, Xiang; Zhang, Baoxian; Mouftah, Hussein (Computer communications, 2020)
Broadcasting is a fundamental problem for wireless multi-hop networks such as wireless ad hoc and sensor networks. In this paper, we study distributed robust time-efficient global broadcasting for SINR-based (i.e., Signal-to-Interference-plus-Noise-Ratio-based) multi-channel wireless multihop networks subject to channel disruption. In this study, we make the following assumptions: i) for successful packet reception, the SINR at receivers must exceed a certain threshold; ii) an adversary exists in the network, which uniformly and randomly chooses t > 0 channels to disrupt from total F > 1 available channels in every round. To address the broadcasting issue in such networks, we first propose a degree-aware broadcasting algorithm and then propose a degree-independent broadcasting algorithm. The proposed algorithms elaborately integrate distributed channel selection and transmission scheduling at different nodes while considering the following factors: the impact of SINR constraint, availability of channels, sending probability on selected channel, presence of adversary, with and without node degree information. We present the detailed design of the two algorithms. We deduce their worst-case time performance to accomplish the task of global broadcasting with high probability. We further prove that both algorithms can still preserve the same time performance under more powerful oblivious adversary and weakly adaptive adversary. Simulation results show that the proposed algorithms have satisfactory average-case time performance.